Two-year results of a combined regimen of aflibercept treatment in three types of choroidal neovascular membrane in the wet form of age-related macular degeneration: Real-life evidence in the Czech Republic. Issue 5 (September 2021) - Stepanov, Alexandr; Nemcansky, Jan; Veith, Miroslav; Manethova, Katerina; Stredova, Marketa; Pencak, Martin; Tarkova, Anna; Studnicka, Jan
Aim: To present the results of a 2-year therapy with aflibercept in real-life practice in a mixed regimen in patients with a neovascular form of age-related macular degeneration (nAMD) and to evaluate the treatment response of various types of choroidal neovascular membranes (CNV) – occult (Type 1), classic (Type 2) and minimally classic (Type 4). Methods: This was a multicentric, prospective, observational study of a series of cases. Patients diagnosed with the wet form of AMD were treated in a fixed regimen (3 injections at intervals of 1 month and then injections at 8-week intervals) in the first year, and in a pro re nata regimen (PRN) in the second year. The period of investigation was 24 months. The development of the best corrected visual acuity (BCVA) was evaluated by means of ETDRS optotypes (Early Treatment Diabetic Retinopathy Study) and the central retinal thickness (CRT). Measurements were performed prior to the commencement of therapy and then after 4, 8, 12, 16, 20 and 24 months. Results: The therapeutically naïve group consisted of 135 eyes of 135 patients. Sixty-one eyes suffered from CNV of the 1st type, 50 eyes from CNV of the 2nd type and 24 eyes from CNV of the 4th type. The average baseline of BCVA ± SD in Type 1 CNV was 56.1 ± 10.8 letters of ETDRS, and then, respectively, 62.2 ± 12.9 letters, 62.8 ± 15.1 letters and 59.4 ± 13.2 letters after 4, 12 and 24 months. The average baseline value of CRT ± SD for Type 1 CNV was 442.4 ± 194.9 µm, and then 302.5 ± 144.4 µm, 277.7 ± 106.5 µm and 327.6 ± 138.6 µm at months 4, 12 and 24. The average baseline value of BCVA ± SD in Type 2 CNV was 55.6 ± 9.9 letters of ETDRS, and then 62.5 ± 11.1 letters, 62.5 ± 14.2 letters and 60.6 ± 15.1 letters after 4, 12 and 24 months. The average baseline value of CRT ± SD in Type 2 CNV was 446.8 ± 159.1 µm, and then 327.4 ± 127.0 µm, 316.7 ± 139.1 µm and 352.5 ± 132.4 µm at 4, 12 and 24 months. In Type 4 CNV, the average baseline value of BCVA ± SD was 56.7 ± 9.0 letters of ETDRS, and then 59.1 ± 10.6 letters, 59.2 ± 12.6 letters and 58 ± 8.8 letters after 4, 12 and 24 months. The average baseline value of CRT ± SD in Type 4 CNV was 492.1 ± 187.0 µm, and then 333.3 ± 137.5 µm, 326.7 ± 122.4 µm and 328.4 ± 132 µm at months 4, 12 and 24. All these changes were statistically significant ( p < 0.05). Conclusion: Therapy with aflibercept in a mixed regimen in patients with the wet form of AMD during the investigation resulted in a statistically significant improvement in BCVA and decrease in CRT in both the occult and classic type of CNV. Both the functional and anatomical response to therapy was worse in the minimally classic type (Type 4) of CNV. Summary declaration: Patients suffering from the neovascular form of age-related macular degeneration were treated with aflibercept in a mixed regimen (fixed in the first year and PRN in the second year). After 24 months of examination, a significant improvement of both morphological and functional results was observed in three types of choroidal neovascular membrane.